Kedudukan Hukum Mahar “Sunreng” dalam Perkawinan Bugis Makassar - A. Asmah; Andi Istiana Inayah Dwi Putri (Kertha Wicaksana, 2024)
This study aims to determine and analyze the implementation of the provision of land dowry in marriage according to national defense law, as well as the legal protection status of ownership of land rights in marriage dowry in Tanralili District, Maros Regency. In addition, it also aims to find out and analyze legal protection for women who receive dowry land in marriage in Tanralili District, Maros Regency. In addition to field research, namely open interviews with a number of local government officials such as the Head of BPN Maros Regency, Tanralili Sub-District, Head of KUA Tanralili District, as well as questions and answers with several residents who married with land as their dowry, a literature study was also conducted (Library Research) by studying related laws and regulations, books, journals, and articles obtained through the internet. Data analysis is carried out using qualitative and normative analysis techniques. The result of this study is that the implementation of dowry in marriage of national land law is valid or permissible as long as legal certainty in terms of certificates is submitted at the time of marriage contract if and according to national land law if registered with the national land office by first proving by a deed of grant made by the Land Deed Making Officer (PPAT). And Legal protection for women who receive land, the provision of dowry in marriage in Tanralili District, Maros Regency, which is the strongest on land, is a certificate made by the local land office, further suggestion that the granting of dowry in marriage can be recognized for its implementation according to national land law.